Tata Letak Instrumen dalam Konteks Strategi Pengajaran dan Pertunjukan Musik Gamelan Bali di Canterbury University, New Zealand - I Made Kartawan; Roger Buckton (Mudra Jurnal Seni Budaya, 2022)
This article addresses the role of the layout of the instruments in rehearsal and on stage as a factor to help achieve the goal of nabuh with the University of Canterbury gamelan group. It is focused on how the layout of the instruments effects the learning and performing process. No literature on this topic was located and the terminology and concepts used in this paper have been developed for the purpose of this research. This study was guided by a qualitative case study approach using data that was collected through questionnaires, interviews and participant observation. Based on the findings, the exploration of the layout of the instruments offered various alternatives in assisting coordination among musicians in rehearsals and performance contexts and contributed to the achievement of the goal nabuh.